Evolutionary computation in combinatorial optimization : 18th European Conference, EvoCOP 2018, Parma, Italy, April 4-6, 2018, Proceedings /: 18th European Conference, EvoCOP 2018, Parma, Italy, April 4-6, 2018, Proceedings. (2018) - Unknown
No abstract available